Creativity Efforts of Sasirangan Fabric Artisans in Increasing Sales in Islamic Economics Terms - Annisa Anisykurlillah; Muhammad Rizali; El Wafa, Faqih; Muhammad Saleh (LP2M IAIN Palopo, 2024)
This research is motivated by the important role of sasirangan cloth artisan in preserving local culture with diverse creativity. The aim of this research is to determine creativity in an effort to increase sales in terms of Islamic economics and the obstacles faced by artisan. This research is field research, with a qualitative approach. The research location is Sasirangan Village, Banjarmasin City. Data was obtained using interviews, with data processing techniques, then analyzed qualitatively and referring to the theoretical basis. The research results obtained are first, the creativity of Sasirangan cloth artisan in Sasirangan Village in an effort to increase sales in terms of Islamic economics is painting their own motifs, adding creations, participating in exhibitions, modifying motifs, using natural materials. Second, the obstacles faced by sasirangan cloth business artisan in Sasirangan Village in carrying out creativity are labor resource constraints, policy constraints regarding time regulations and constraints on raw materials, synthetic and natural dyes used in dyeing sasirangan cloth.